2018
DOI: 10.1186/s12913-018-3379-0
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers to sexual health service use among university students: a qualitative descriptive study using the Theoretical Domains Framework and COM-B model

Abstract: BackgroundUniversity students are within the age group at highest risk for acquiring sexually transmitted infections and other negative health outcomes. Despite the availability of sexual health services at university health centres to promote sexual health, many students delay or avoid seeking care. This study aimed to identify the perceived barriers and enablers to sexual health service use among university undergraduate students.MethodsWe used a qualitative descriptive design to conduct semi-structured focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 46 publications
1
73
0
2
Order By: Relevance
“…Behaviour Change Techniques are the active, observable and replicable components that make up an intervention. COM-B/BCW have been used successfully for behavioural analysis and to design interventions in both health and non-health-related elds [26,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], but to our knowledge, has been used in only one study of TB on contact tracing in a low-resource setting, to identify barriers and facilitators and to tailor interventions to improve contact investigation in Kampala [26]. In the qualitative arm, to understand the challenges in recognising and testing for TB in admitted children we analysed data from: i) semi-structured interviews, small-group discussions and key informant interviews with front line health workers and mid-level managers; ii) observations of TB trainings, sensitisation meetings, policy meetings, and hospital practices, and iii) desk review of guidelines, job aides and policy documents, which have been reported elsewhere [31].…”
Section: Using the Behaviour Change Wheel To Guide Intervention Designmentioning
confidence: 99%
“…Behaviour Change Techniques are the active, observable and replicable components that make up an intervention. COM-B/BCW have been used successfully for behavioural analysis and to design interventions in both health and non-health-related elds [26,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], but to our knowledge, has been used in only one study of TB on contact tracing in a low-resource setting, to identify barriers and facilitators and to tailor interventions to improve contact investigation in Kampala [26]. In the qualitative arm, to understand the challenges in recognising and testing for TB in admitted children we analysed data from: i) semi-structured interviews, small-group discussions and key informant interviews with front line health workers and mid-level managers; ii) observations of TB trainings, sensitisation meetings, policy meetings, and hospital practices, and iii) desk review of guidelines, job aides and policy documents, which have been reported elsewhere [31].…”
Section: Using the Behaviour Change Wheel To Guide Intervention Designmentioning
confidence: 99%
“…The TDF [38], compromises 14 domains, each of which corresponds to a COM-B component and also representing a range of theory-based barriers and facilitators to behaviour [37]. The COM-B model and TDF have been used by several studies to explore barriers and facilitators to behaviour change in sexual health [42], physical activity in obese pregnant women [43] and reducing sugar [40]…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…To our knowledge, this is the first study investigating adherence to the MIND diet at midlife (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) years old) in a Mediterranean and non-Mediterranean country. This study addresses this gap in the literature and highlights the perceived barriers and facilitators to adhering to a diet that may promote brain health at midlife and compares those barriers and facilitators to those living in Northern Ireland.…”
Section: Introductionmentioning
confidence: 99%
“…27 This combination of theoretical constructs has been used in a variety of settings to understand, explain and improve practice but not before in cardiac surgical bleeding management. 28,29 Current intra-operative bleeding management practice in Australian cardiac surgery units is not understood. The barriers and enablers to implementing effective bleeding management strategies, including the relationships between key stakeholders, and institutional support, likely impact on the uptake of evidence-based practice.…”
Section: Introductionmentioning
confidence: 99%